Apprenticeship Training in European Countries. The Lessons for Canada - Weiermair, Klaus (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
This paper investigates environmental conditions conducive to apprenticeship training; examines various government reactions in this field; discusses the problems and deficiencies of apprenticeship training in Canada, and analyzes the usefulness of European labour market measures to be employed in this country.